SBA-Pr-IS-MN-DM: a new fluorescent chemosensor for trace detection of silver in aqueous solutions - Ghodsi Mohammadi Ziarani; Fatemeh Mohajer; Fatemeh Javadi; Alireza Badiei; Rajender S. Varma (Scientific Reports)
Abstract Initially, SBA-Propyl-Isatin-Malononitrile (SBA-Pr-IS-MN) was prepared by the reaction of SBA-Pr-Cl with IS-MN, which was synthesized by the reaction of isatin and malononitrile. This organic and inorganic hybrid material can be functionalized by the sequential reaction with dimedone to obtain the target product SBA-Pr-Is-MN-DM, which was investigated as a chemosensor by fluorescence spectroscopy to detect trace amount of Ag+ among several other cations in aqueous media.